Impact of perception reduction of employment opportunities on employment pressure of college students under COVID-19 epidemic–joint moderating effects of employment policy support and job-searching self-efficacy - Yang, Shiyuan; Yang, Jinxiu; Yue, Longhua; Xu, Jingfei; Liu, Xingyu; Li, Wei; Cheng, Hao; He, Guorong (Frontiers in Psychology, 2022)
Based on the stress interaction theory, this research constructed a model to study the joint moderating effects of the perception reduction of employment opportunities on college students' employment pressure under the COVID-19 epidemic. With two moderating variables introduced, employment policy support and Job-searching self-efficacy, this research studied the mechanism and boundary conditions of perception reduction of employment opportunities on college students' employment pressure from both individual and environmental aspects. The study found that during the epidemic if college students perceived fewer employment opportunities, they could have greater employment pressure from themselves, universities and families; and that under the joint moderation of employment policy support and job-searching self-efficacy, the reduction of employment opportunities during the epidemic and the employment pressure of college students, universities, and families were connected, with different adjustment mechanisms. Based on empirical data, this research can provide theoretical enlightenment and practical guidance for the government, universities and families to alleviate the employment pressure of college students during the epidemic.